An ex-vivo model for the biomechanical assessment of cement discoplasty - Ghandour, Salim; Pazarlis, Konstantinos; Lewin, Susanne; Isaksson, Per; Försth, Peter; Persson, Cecilia (Frontiers in Bioengineering and Biotechnology, 2022)
Percutaneous Cement Discoplasty (PCD) is a surgical technique developed to relieve pain in patients with advanced degenerative disc disease characterized by a vacuum phenomenon. It has been hypothesized that injecting bone cement into the disc improves the overall stability of the spinal segment. However, there is limited knowledge on the biomechanics of the spine postoperatively and a lack of models to assess the effect of PCD ex-vivo. This study aimed to develop a biomechanical model to study PCD in a repeatable and clinically relevant manner. Eleven ovine functional spinal units were dissected and tested under compression in three conditions: healthy, injured and treated. Injury was induced by a papain buffer and the treatment was conducted using PMMA cement. Each sample was scanned with micro-computed tomography (CT) and segmented for the three conditions. Similar cement volumes (in %) were injected in the ovine samples compared to volumes measured on clinical PCD CT images. Anterior and posterior disc heights decreased on average by 22.5% and 23.9% after injury. After treatment, the anterior and posterior disc height was restored on average to 98.5% and 83.6%, respectively, of their original healthy height. Compression testing showed a similar stiffness behavior between samples in the same group. A decrease of 51.5% in segment stiffness was found after injury, as expected. The following PCD treatment was found to result in a restoration of stiffness – showing only a difference of 5% in comparison to the uninjured state. The developed ex-vivo model gave an adequate representation of the clinical vacuum phenomena in terms of volume, and a repeatable mechanical response between samples. Discoplasty treatment was found to give a restoration in stiffness after injury. The data presented confirm the effectiveness of the PCD procedure in terms of restoration of axial stiffness in the spinal segment. The model can be used in the future to test more complex loading scenarios, novel materials, and different surgical techniques